Hubungan Lama Penyakit Ginjal Kronis dengan Kejadian Karies Gigi - Hamka, Nur Rahmi Qonita Putri; Jelita, Helena; Kahanjak, Donna Novina (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Chronic kidney disease (CKD) affects >10% of the world's population. The incidence of CKD in Indonesia reached 713,783 cases, with a proportion of 2,850 hemodialysis patients. CKD is a disease that occurs when the kidney nephrons are damaged due to the influence of various diseases. Systemic complications of CKD can affect dental and oral health, such as salivary flow, xerostomia, calculus, and dental caries. Dental caries ranks highest among dental and oral disease problems. This study aims to determine the correlation between the duration of chronic kidney disease and dental caries. This is an analytic-observational study with a cross-sectional approach. Bivariate analysis using the Pearson correlation test. On average, patient has been diagnosed with CKD for 20 months and the population DMF-T index is 10.88. The duration of chronic kidney disease is not related to the incidence of dental caries, with a value of p = 0.898 (p > 0.05).